Treinamento de potência com resistência elástica para idosos: uma revisão de escopo - (:unkn) unknown (FEFF - Faculdade de Educação Física e Fisioterapia, 2025)
The aging process causes a considerable reduction in muscle power when compared to the capacity for force production, which impairs the functional capacity of the older people. In this scenario, the practice of power training has been recommended to combat such losses. Among the ways to apply this training, little has been investigated regarding the use of elastic resistance. Thus, this study aimed to investigate the effects of power training with elastic resistance on the functional capacity and power of old people, as well as to compare the effects of this type of training with traditional strength training on the power and functional capacity of old people. This is a scoping review with a qualitative and exploratory approach, carried out in databases such as PubMed, SPORTDiscus and Web of Science. The inclusion criteria considered were: studies with old people (≥ 60 years) undergoing power training with elastic resistance, comparison with conventional and/or control strength training groups, with functional capacity and muscle power tests being evaluated. After the entire selection process, 4 studies were included in this review, all of which involved women aged between 67 and 78 years old. The studies analyzed demonstrated that power training with elastic resistance improved functional capacity, with emphasis on an increase of up to 32.56% in the SPPB score, a reduction of 33.56% in the time of the chair rise test in 5 repetitions, and improvements in handgrip strength of up to 26.5%. Regarding muscle power, increases in the peak torque of the knee extensors of up to 39.17% were observed. Compared to traditional strength training, training with elastic bands showed superior performance in several functional and muscular parameters, in addition to being more accessible. Thus, power training with elastic resistance is efficient in improving the functional capacity and muscular power of older women and can help old people reduce disability, improve the performance of daily life activities and reduce the risk of mortality.
Keywords: Envelhecimento; Força explosiva; Faixa elástica; CIENCIAS DA SAUDE: EDUCACAO FISICA; .; .